Remineralization of early enamel caries lesions using self-assembling peptides P11-4: Systematic review and meta-analysis - Aparna B K; Yashoda R; Manjunath P Puranik (Elsevier, 2022)
Objectives: To compare the effectiveness of self-assembling peptides (SAP) P11-4 in remineralising early enamel lesions to that of other remineralising agents. Methods: This review was conducted according to PRISMA guidelines. MEDLINE (PubMed), Cochrane and Google Scholar databases were searched up to June 2021. For qualitative analysis, randomised controlled trials and in-vitro investigations were included. For quantitative synthesis, randomised controlled trials with comparable outcomes were used. The risk of bias assessment and meta-analysis were carried out using the RoB 2 tool and RevMan software. Results: This systematic review and meta-analysis included a total of 12 in-vitro studies and 6 randomised controlled trials. SAP P11-4 had superior effect in remineralising early enamel lesions compared to control groups. In Meta-analysis, SAP P11-4 showed superior remineralization when measured using the VAS data {SMD [-0.61 (−0.88, −0.34)]}; significant caries regression according to Nyvad criteria {OR [0.16(0.03,0.88)]}; and significant improvement in the extent of demineralization in test group {SMD [-0.67 (−1.29, −0.05)]} when measured for fluorescence in comparison with other remineralising agents. On the other hand, morphometric measurements {MD [-0.12(-0.25, −0.00)]} and ICDAS criteria {OR [4.91(0.80, 30.22)]} found no difference among the tested materials. Conclusions: Both in-vitro and in-vivo studies showed evidence of superior biomimetic remineralization in the SAP P11-4 group compared to other remineralising agents. However, long term studies are necessary to confirm its suitability in clinical use.